Transcriptoma da interação de tangerina satsuma (Citrus unshiu) e laranja doce Hamlin (Citrus sinensis) infectadas com Xanthomonas citri subsp. citri, agente causal do cancro cítrico - Murata, Mayara Mari [UNESP] (2013)
Citrus canker, caused by Xanthomonas citri subsp. citri (Xac), is a one of the most important disease affecting citrus production worldwide and attacks a wide range of commercial species of citrus trees, causing significant losses in producing countries. Hamlin sweet orange (Citrus sinensis) is canker-sensitive, while Satsuma mandarin (Citrus unshiu) is canker-resistant. To understand the molecular mechanisms underlying the differences in responses to Xac, transcriptional profiles of these two genotypes following Xac attack were compared by RNA-Seq (Illumina). The purpose of this study was to examine simultaneous changes in gene expression profile during the early stages (24, 48 and 72 hpi) of citrus canker infection in Satsuma and Hamlin. A total of 5673 and 6231 up-regulated transcripts were identified at 24, 48 and 72 hpi in Satsuma and Hamlin, respectively, while 3982 and 7944 were down-regulated. Of these, 52 transcripts were up-regulated in common between both genotypes. These genes in common are related to basic defense against Xac, because there are genes involved in patogen perception and recognition, transcription factors and genes related to plant defense, such as glucanases and proteinases. Among up-regulated genes expressed only in Satsuma, aspartic proteinase was highlighted. This protein presented the highest gene expression 24 hpi and it can be involved in Satsuma resistance, since the expression of this protein was less pronounced and delayed in Hamlin. Another opposite response between these two genotypes was the expression of genes related to cell wall. Such genes were pectato lyase, extensin, cellulose sinthase, and xiloglucano endotransglycosilase. The genes were up-regulated in Satsuma, while in Hamlin, they were down-regulated. For genes related to plant defense, both genotypes up- regulated pathogenesis-related proteins, especially 72 hpi. However, the expression of these genes did not prevent the symptoms in ...